2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31067
|View full text |Cite
|
Sign up to set email alerts
|

Technical Communication Across the ME Curriculum at Rose-Hulman

Abstract: is a professor of Mechanical Engineering at Rose-Hulman Institute of Technology. He teaches courses in fluid mechanics, thermodynamics, measurement systems, and aerospace engineering. He was a USAF officer for 13 years before joining Rose-Hulman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…In keeping with Philosophy 2, some studies demonstrated that the magnitude of the effects noted above depended on the attributes of the audience, such as their spelling ability or their professional background [37], [38], [39], while others demonstrated that communication quality is "in the eye of the beholder" [46], [47]. Philosophy 2 is also consistent with examples in engineering education, such as how departments teach memo writing [48] or account for the influence of professional communities of practice on student communication needs [49]. Philosophy 3 captures the idea that technical communication always matters, but to varying degrees depending on the situation.…”
Section: Three Philosophiesmentioning
confidence: 59%
“…In keeping with Philosophy 2, some studies demonstrated that the magnitude of the effects noted above depended on the attributes of the audience, such as their spelling ability or their professional background [37], [38], [39], while others demonstrated that communication quality is "in the eye of the beholder" [46], [47]. Philosophy 2 is also consistent with examples in engineering education, such as how departments teach memo writing [48] or account for the influence of professional communities of practice on student communication needs [49]. Philosophy 3 captures the idea that technical communication always matters, but to varying degrees depending on the situation.…”
Section: Three Philosophiesmentioning
confidence: 59%
“…We then categorized that instruction by genre, including memos, presentations, reports, and technical drawings. Using memos as a starting point, we then identified threshold concepts, or core things students needed to know to compose successful memos [4]. These threshold concepts represent the communication tasks and skills that the department expects students to transfer across courses.…”
Section: The Impact Of Scaffolded Writing Instruction On Follow-up Course Assignmentsmentioning
confidence: 99%
“…Scaffolding centers on intentionally connecting graded events (e.g., capstone projects or research papers) with technical communication components across courses, either within the same semester or longitudinally across semesters. Scaffolding events across semesters offers several advantages, to include the ability for students to benchmark against previous performance and continually add to a body of increasingly complex work while simultaneously enhancing technical communication skills (Bercich et al 2018). Currently, all technical communication graded events in our program's curriculum occur discretely within one course except for our senior design capstone courses (EV490/EV491), which cover two semesters.…”
Section: Opportunities For Continuous Improvement Future Work and Application At Other Universitiesmentioning
confidence: 99%
“…Engineers need strong communication skills to effectively convey ideas to a range of audiences (Kamarudin et al 2012). Many studies have identified communication as one of the most important transferrable employment skills -one that often influences job performance and career advancement (Grant and Dickson 2006;Leydens et al 2008;Poe et al 2010;Lopes et al 2015;Bercich et al 2018;Young and Ashman 2019). Despite the importance of communication skills, several studies have identified communication-related shortcomings in recent graduates, such as convoluted writing, imprecise or inaccurate content, and an inability to meaningfully Several approaches to coupling general communication skills and discipline-specific technical communication skills exist.…”
Section: Introductionmentioning
confidence: 99%